PERANAN UREA DAN SP-36 DALAM MENINGKATAN PERTUMBUHAN TANAMAN SORGUM DI LAHAN MARGINAL - Wikantyasa, Boma; Dewi, Indya; Adriani, Dewi Erika (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
The Urea and SP-36 dosages in this study mean to discover how it affects sorghum growth in Ultisol soil, using a factorial randomized block design with two components employed in the investigation. The first consideration is the urea dose (u), which consists of four treatment levels.:  = 100 kg ,  = 150 kg ,  = 200 kg , and   = 250 kg . The second factor is the SP-36 dose consisting of 3 levels: = 100 kg , = 150 kg , and  = 200 kg . The observations include plant height (cm), leaf area per plant ( ), shoot dry weight (g), root dry weight (g), final vegetative shoot-root ratio, and final generative shoot-root ratio. The results indicate that the interaction of Urea and SP-36 did not significantly affect all variables.  However, the single factor of Urea significantly affected the final vegetative shoot-root ratio, while SP-36 significantly affected the plant height at 63 days after sowing.